TINJAUAN HUKUM ISLAM TERHADAP PELAKSANAAN UNDIAN BERHADIAH (STUDI KASUS TOKO ASRIN SIREGAR PIDOLI DOLOK KECAMATAN PANYABUNGAN) - Yuli Anti; Nabila Zakiyah; Rini Maya Saroh Siregar (TAHKIM, 2025)
This study examines the Islamic legal review of the implementation of a prize draw at the Asrin Siregar Shop, Pidoli Dolok, Panyabungan District. The implementation of the Prize Draw is to attract consumers by creating a member program in the Prize Draw. Prizes are given if they have sufficient points determined by the Asrin Siregar Shop. The requirements to be able to participate in the Prize Draw, consumers must complete the administration and pay Rp10,000. In purchasing an item with a nominal value of Rp20,000, they will get one point, while to get a prize they must have 200 points. This study is a field study, located at the Asrin Pidoli Shop, Panyabungan District. The results of this study indicate that the form of the draw at the Asrin Siregar Shop is a draw that is prohibited in Islamic law, namely a draw with conditions and a draw with costs, and the draw is included in one of the draws that contains elements of harm or damage. Keywords: ju'alah, prize draw, maisir, islamic law.